2018
DOI: 10.1002/jcop.22116
|View full text |Cite
|
Sign up to set email alerts
|

Does having a similar disability matter for match outcomes?: A randomized study of matching mentors and mentees by visual impairment

Abstract: Mentoring is modestly effective for youth with a chronic illness or physical disability; however, program effectiveness may be enhanced when mentors and mentees are matched on shared interests and experiences. To test this hypothesis, mentees were randomly assigned to having a mentor with or without visual impairment (VI). Results showed that mentors without VI were younger and more likely to work or be educated in a helping profession and less likely to have a fixed mindset and extremely high positive expecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…Finally, foster youth are more likely to be matched with a mentor who has professional experience in a helping profession such as working in the fields of social work, mental health, childcare or daycare, clergy, or education, among others. This practice is in alignment with findings suggesting that mentors who have a background in a helping profession may be more likely to have a positive impact on match longevity (Heppe, Kupersmidt, Kef, & Schuengel, ) and youth outcomes (DuBois et al., ). Mentoring programs appear to take into consideration the unique needs and challenges of youth in foster care when recruiting and matching mentors to youth in foster care.…”
Section: Discussionsupporting
confidence: 84%
“…Finally, foster youth are more likely to be matched with a mentor who has professional experience in a helping profession such as working in the fields of social work, mental health, childcare or daycare, clergy, or education, among others. This practice is in alignment with findings suggesting that mentors who have a background in a helping profession may be more likely to have a positive impact on match longevity (Heppe, Kupersmidt, Kef, & Schuengel, ) and youth outcomes (DuBois et al., ). Mentoring programs appear to take into consideration the unique needs and challenges of youth in foster care when recruiting and matching mentors to youth in foster care.…”
Section: Discussionsupporting
confidence: 84%
“…The study followed a randomized controlled trial design with two experimental groups and one care-as-usual group. Full details of the study protocol and the content of the mentoring program were reported in studies by Hepp et al [47,48]. Randomization stratification on geographic proximity to ensure equal allocation to regions as well as to reduce travel time for mentors to the homes of mentees was conducted by an independent researcher with the use of a computerized random number generator.…”
Section: Methodsmentioning
confidence: 99%
“…Only 8 mentors were not employed at the moment and 34% of those with a job were employed in a helping profession. More information about the selection process and background characteristics of mentors can be found in a recent study [48].…”
Section: Mentoring Programmentioning
confidence: 99%
“…This current study is part of a larger evaluation study on the efficacy of a community-based mentoring program, called Mentor Support, for adolescents with VI (Heppe et al, 2015;Heppe et al, 2018;Heppe et al, 2019). In a previous report, the efficacy of this community-based mentoring program on social participation outcomes and the effect of match similarity with respect to disability was tested (Heppe et al, 2019).…”
Section: Current Studymentioning
confidence: 99%